2004
DOI: 10.1007/s10456-004-4182-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathological angiogenesis is reduced by targeting pericytes via the NG2 proteoglycan

Abstract: The NG2 proteoglycan is expressed by nascent pericytes during the early stages of angiogenesis. To investigate the functional role of NG2 in neovascularization, we have compared pathological retinal and corneal angiogenesis in wild type and NG2 null mice. During ischemic retinal neovascularization, ectopic vessels protruding into the vitreous occur twice as frequently in wild type retinas as in NG2 null retinas. In the NG2 knock-out retina, proliferation of both pericytes and endothelial cells is significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(179 citation statements)
references
References 101 publications
(104 reference statements)
10
165
0
1
Order By: Relevance
“…12 NG2, the rat homologue of MCSP, is expressed by nascent pericytes during early stages of angiogenesis and plays an important role in neovascularization. 13 In line with these findings, NG2 knock-out mice show a significantly reduced proliferation of pericytes and endothelial cells within the retina and cornea. 13 Glioblastoma multiforme tumors transfected with NG2, showed a significantly increased neovascularization rate with a higher vascular density than control tumors in a rat model.…”
Section: Abstract: Mcsp; Melanoma; Peptide; T Helper Cells; Tumor Anmentioning
confidence: 55%
See 1 more Smart Citation
“…12 NG2, the rat homologue of MCSP, is expressed by nascent pericytes during early stages of angiogenesis and plays an important role in neovascularization. 13 In line with these findings, NG2 knock-out mice show a significantly reduced proliferation of pericytes and endothelial cells within the retina and cornea. 13 Glioblastoma multiforme tumors transfected with NG2, showed a significantly increased neovascularization rate with a higher vascular density than control tumors in a rat model.…”
Section: Abstract: Mcsp; Melanoma; Peptide; T Helper Cells; Tumor Anmentioning
confidence: 55%
“…13 In line with these findings, NG2 knock-out mice show a significantly reduced proliferation of pericytes and endothelial cells within the retina and cornea. 13 Glioblastoma multiforme tumors transfected with NG2, showed a significantly increased neovascularization rate with a higher vascular density than control tumors in a rat model. This accelerated angiogenesis was accompanied by a dramatic increase in tumor growth.…”
mentioning
confidence: 55%
“…In NG2 knock-out mice, proliferation of both pericytes and endothelial cells in retina in response to hypoxia is significantly reduced. 30 There are several possible mechanisms by which NG2 regulates angiogenesis; NG2 has been shown to bind directly to basic fibroblast growth factor and platelet-derived growth factor AA (PDGF-AA), and may enhance interaction of these growth factors with cell surface receptors. 16 In the present study, we showed an overexpression of NG2 in vascular-associated pericytes at 3 weeks, which is spatiotemporally expressed with MMPs, VEGF, and TJPs.…”
Section: Discussionmentioning
confidence: 99%
“…NG2 regulates cell proliferation, migration, spreading, and adhesion in melanomas, gliomas, oligodendrocyte progenitors, and pericytes 16,17,20,21 and increases metastasis of melanoma cells. 20 It has never been implicated in apoptosis.…”
Section: Discussionmentioning
confidence: 99%